El matrimonio gitano ante el Tribunal Europeo de Derechos Humanos. El caso Muñoz Díaz contra España (STEDH de 8 de diciembre de 2009) - Gaya Sicilia, Regina (Revista de Derecho, 2020)
Commentary on the case of the European Court of Human Rights of December 8, 2009. The Spanish state is condemned to pay compensation to a Roma woman for having discriminated by failing to acknowledge a widow’s pension. The background of the case and related doctrinal issues have been the subject of a previous article published in this journal (Vol. 10/2009, pp. 291-321).